First record of megaleporinus piavussu (characiformes: anostomidae) from Argentina - Benitez, Mauricio Fabián (2020)
Megaleporinus obtusidens and M. macrocephalus were known to be the only representatives of the genus in Argentina and the former was also the only species recorded from the Paraná river in the country. Recent collection campaigns at Paraná River in Argentina allowed us to identify for the first time the presence of Megaleporinus piavussu.